Mesospheric wind disturbances due to gravity waves near the Antarctica Peninsula. Issue 14 (29th July 2013) - Wu, Qian; Chen, Zeyu; Mitchell, Nick; Fritts, D.; Iimura, H.
Abstract : [1] Based on austral winter mesospheric wind observations from three closely deployed Antarctic Peninsula stations (King George Island, Palmer, and Rothera), mesospheric wind disturbances induced by gravity waves are examined. The mesospheric winds to the west of the Antarctic Peninsula below 88 km were affected by gravity waves, while the winds on the east side of the peninsula were unperturbed. The gravity waves are most likely generated by orographic features of the peninsula. Because the strong westerly stratospheric wind filtered out all eastward propagating waves, only westward propagating waves can reach the mesosphere on the west side of the peninsula. This data set shows the strong gravity wave effect on small scales. Hence, the mesospheric wind data at one station may not be representative of the region for global waves like tides. Small local features can greatly affect the mesospheric winds and may impact the interpretation of global waves. High‐density deployment of mesospheric wind instruments may be needed in some cases. Key Points: Gravity waves induce mesospheric structure near Antarctica Peninsula lower altitude winds filtered eastward waves semidiurnal tide structure affected